Measurement of transcribed human X-chromosomal DNA sequences transferred to rodent cells by chromosome-mediated gene transfer. - McBride, O W (1982)
Transfer of genetic information can be effected by incubation of cultured eucaryotic cells with isolated metaphase chromosomes. In most cases, a resulting transformed cell contains only a fragment of a donor chromosome. The amount of transferred donor DNA has been quantified in 11 independent mouse A9 transformants by nucleic acid hybridization analysis. Each transformant had been selected for hprt (hypoxanthine phosphoribosyltransferase; EC 2.4.2.8) transfer and contained part of the human X chromosome. A labeled probe of transcribed human X-chromosomal DNA was prepared by hybridization of nick-translated unique-sequence human DNA with whole cellular RNA from a human-mouse hybrid cell line, A9/HRBC2-A, containing a single human chromosome., X. The amount of human X-chromosomal DNA in the transformants was quantitated by comparing the hybridization of this probe with transformant and A9/HRBC2-A DNAs. Two unstable transformants which had a microscopically detectable donor chromosome fragment contained 15% of the human X-chromosomal single-copy DNA. Four other unstable transformants contained 4 to 7% of human X-chromosomal DNA sequences. The transferred DNA was below the level of detection in three other unstable and in all three stable transformants. We conclude that the initial transfer event can introduce a substantial amount of genetic information but only smaller amounts of DNA are stably incorporated by integration.